Experiences with VHA care: a qualitative study of U.S. women veterans with self-reported trauma histories - Shannon M. Kehle-Forbes; Eileen M. Harwood; Michele R. Spoont; Nina A. Sayer; Heather Gerould; Maureen Murdoch (BMC, 2017)
Abstract Background Women veterans in the United States, particularly those with posttraumatic stress disorder (PTSD) or a history of military sexual assault, have unique health care needs, but their minority status in the US Veterans Health Administration (VHA) has led to documented healthcare disparities when compared to men. This study's objective was to obtain a richer understanding of the challenges and successes encountered by women veterans with self-reported service-related trauma histories (particularly those with a history of military sexual assault and/or posttraumatic stress symptomology) receiving VHA care. Methods Thirty-seven female Vietnam and post-Vietnam (1975-1998) era veterans were randomly selected from a cohort of PTSD disability benefit applicants to complete semi-structured interviews in 2011-2012. Grounded-theory informed procedures were used to identify interview themes; differences between veterans with and without a history of military sexual assault were examined through constant comparison. Results At the time of the interviews, many women believed that VHA was falling short of meeting women veterans' needs (e.g., lack of women-only mental health programming). Also common, but particularly among those with a military sexual assault history, was the perception that VHA's environment was unwelcoming; being "surrounded by men" yielded emotions ranging from discomfort and mistrust to severe anxiety. A few veterans reported recent positive changes and offered additional suggestions for improvement. Conclusions Findings suggest that while at the time of the interviews gains had been made in the delivery of gender-sensitive outpatient medical care, women veterans with a history of military sexual assault and/or posttraumatic stress symptomology perceived that they were not receiving the same quality of care as male veterans.